Characteristics Of Head Injured Patients : Literatur Review - Sasya Zulian Nurfalah; Reeny Purnamasari Juhamran; Muhammad Fadli Said (Jurnal EduHealth, 2024)
According to the World Health Organization (WHO) report, every year around 1.2 million people die diagnosed with serious head injuries, namely as a result of traffic accidents (KLL). Head injuries are one of the leading causes of death and disability worldwide. The study of the characteristics of patients with head injuries is an important aspect in efforts to better understand this condition and improve patient management and care. The aim of this literature review is to determine the characteristics of head injuries in patients. The research method used in this research is Literature Review or literature review. The keywords used are "head injury patients". Internet searches for this research article were carried out by accessing Google Scholar, Pubmed, and ScienceDirect. The results of the study showed that from 15 journals, the characteristics of head injury patients based on age showed significant variations, with the late teens and young adults (aged 17-25 years) being the groups most vulnerable to head injuries, caused by risky behavior such as accidents. traffic.